«We are the last mohicans here, brought up in traditions of our native orthodoxy…»: letters of bishop Alexander (Karpin) to prince A. V. Obolensky (1939–1946) - Tatyana Shevchenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This publication presents letters of bishop of the Finnish Archdiocese of the Constantinopolitan Patriarchate, Alexander (Karpin), to the Russian emigrant of the fi rst wave Prince Alexei Vasilyevich Obolensky (1877?1969). The letters are from the period of 1939?1946. They are kept at the archive of Novo-Valaamskiy monastery of Finland and are published for the fi rst time. Alexey Vasilyevich was a descendant of the ancient family of Obolensky. In Russia, he was actively engaged in social and political activities, being one of the founders of the Society for Russian Antiquity (Rus. Общество ревнителей русской старины). After the October revolution he emigrated to Finland. There he became a benefactor of Russian monasteries in Valaam, Konevets, and Lintula. He carried on an extensive correspondence. His correspondents had varied social status and level of familiarity with spiritual matters. One of the correspondents was bishop Alexander (Karpin). He was elected by the Council of the Finnish Orthodox Church to the see of Vyborg in 1935. Because of the Soviet-Finnish Winter war, Obolensky moved to Stockholm, but continued the correspondence. Bishop Alexander cared for refugees from Karelian Isthmus after 1939, who were settled throughout Finland. The correspondence was of personal nature. It characterises the bishop mainly from his personal side, and not so much as a church-related public “functioner”, but as a devoted Christian, a deeply religious person, aggrieved by the fate of the world in that difficult time of fratricidal wars, growing secularism, large-scalerepression against faith and nonconformism, the person on whose shoulders suddenly fell a heavy burden of responsibility for the believers and the Church in such diffi cult conditions. However, in some letters, the bishop also touched upon problems of church life.